2021
DOI: 10.1016/j.ymthe.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient CD4+ T cell targeting and genetic recombination using engineered CD4+ cell-homing mRNA-LNPs

Abstract: Nucleoside-modified messenger RNA (mRNA)-lipid nanoparticles (LNPs) are the basis for the first two EUA (Emergency Use Authorization) COVID-19 vaccines. The use of nucleoside-modified mRNA as a pharmacological agent opens immense opportunities for therapeutic, prophylactic and diagnostic molecular interventions. In particular, mRNA-based drugs may specifically modulate immune cells, such as T lymphocytes, for immunotherapy of oncologic, infectious and other conditions. The key challenge, however, is that T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 50 publications
2
89
0
1
Order By: Relevance
“…Inhalable or intranasal delivery of antiviral ASOs may be used for pulmonary delivery of ASOs targeting viral respiratory infections [141]. Finally, LNPs are one of the most promising carriers for ASO delivery and can be modified with cell-specific ligands or antibodies for selective ASO delivery to infected tissues-for example, GalNAc for liver cells and anti-CD4 for CD4 + T cells [142]. Growing knowledge and emerging technologies would benefit clinical translation of ASOs and other RNA-based therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalable or intranasal delivery of antiviral ASOs may be used for pulmonary delivery of ASOs targeting viral respiratory infections [141]. Finally, LNPs are one of the most promising carriers for ASO delivery and can be modified with cell-specific ligands or antibodies for selective ASO delivery to infected tissues-for example, GalNAc for liver cells and anti-CD4 for CD4 + T cells [142]. Growing knowledge and emerging technologies would benefit clinical translation of ASOs and other RNA-based therapies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the fast-growing field of cancer immunotherapy, the focus is on modifying and activating immune cells. A recent study [117] showed that conjugating CD4 antibody to LNPs enables specific targeting to and mRNA interventions in CD4+ cells, including T cells. After systemic injection in mice, CD4-targeted radiolabeled mRNA-LNPs accumulated in spleen, providing ∼30-fold higher signal from reporter mRNA in splenic T cells, as compared with non-targeted mRNA-LNPs.…”
Section: Liver Targeting and Beyondmentioning
confidence: 99%
“…Studies led by the Muzykantov laboratory have demonstrated the successful conjugation of antibodies targeting vascular adhesion molecule PECAM-1 or ICAM-1 and re-directing the LNP accumulation away from the liver to the lung [164,165] or VCAM-1 and targeting to the cerebral endothelium during brain edema [165]. A similar approach, using CD-4 antibody conjugated to the surface of the LNP, directed uptake into all T cells (naïve, central, memory, and effector) in both spleen and lymph enabling the possibility to conduct chimeric antigen receptor (CAR) T cell therapy in vivo [166]. Targeting ligands can re-distribute the LNP to extrahepatic sites; however, these examples are only demonstrated in small research scale settings.…”
Section: Breakthrough and Challenges Of Mrna-lnpmentioning
confidence: 99%